Adopting Theories-Based Model Of Information Security Compliance Behaviour For Healthcare Employees In Kingdom Of Saudi Arabia - Tuwayrish S, Alanazi Sultan (2023)
Information security research shows that employees are a source of certain security difficulties in the organization. This frequently happens as a result of disregarding information security policies (ISPs). Therefore, the issue is how to enhance employee information security behaviour so that it complies with the ISPs. This study seeks to advance knowledge about information security compliance behaviour (ISCB) in the Saudi healthcare industry, with a focus on how it may be enhanced from an employee standpoint.